A Multi-Actor-Perspective on Reverse Logistics and Enhanced Circularity of Car Bumper Covers: A Case Study at Volvo Cars - Myklebust, Lea (My University, 2022)
The automotive industry ranks as the third biggest plastic consumer, responsible for 8.8 % of the total plastic demand and 5 % of the post-consumer plastic waste. Today, close to1000 tons of high- quality material from bumper covers alone is discarded at Volvo certified repair shops globally, with Sweden being the biggest market. The vast majority of this material is incinerated with energy recovery. This master thesis project therefore aimed to identify critical factors and enablers for an effective bumper cover recycling and to demonstrate what such a value network can look like in terms of actors involved and material- and information flows. This was done through exploration of the value network and reverse logistics system from a multi actors’ perspective. Interviews was the main source of data. Seven impact factor categories were identified: operational and logistics, technical and quality; economic; people and attitudes; policy and regulations; ownership and control; and information and communication, of which the most important factors are feasibility of material reuse; quality control; employee engagement and competencies; and material flow control. Important enablers to avoid or overcome barriers include active learning, focus on communication and education, and further testing of material tolerances to remove uncertainties relating to technical aspects of material reuse. Recommendations to project coordinators at Volvo include getting familiar with the identified impact factors, and to organize material and production testing to determine tolerances to eliminate existing and restraining uncertainties.
Keywords: Actor system mapping, automotive, circular economy, circular value network, ELV, plastic recycling, plastic waste, reverse logistics, value retention.